The role of Adiponectin and Leptin in Colorectal Cancer and Adenoma: a systematic review and meta-analysis - Iman Elahi Vahed; Mahsa Moshgelgosha; Abdolmajid Kor; Mona Minadi; Faezeh Ebrahimi; Aylar Azhdarian; Mobina Arjmandi; Aida Alamdar; Maede Zare; Niloufar Shabani; Hossein Soltaninejad; Mohammad Rahmanian (BMC Cancer)
Abstract Background Colorectal cancer ranks as the third most frequently diagnosed cancer globally. Adipokines, including adiponectin and leptin, are believed to play a vital role in the development and progression of tumors. This study aimed to clarify the association between circulating adiponectin and leptin concentrations and the risk of colorectal cancer and adenoma. Methods A detailed literature review was conducted in different databases, including Google Scholar, Web of Science, Scopus, and PubMed. Articles measuring serum concentrations of adiponectin and leptin in colorectal adenoma or cancer patients were analyzed. Pooled odds ratios (ORs) and their related 95% confidence intervals (CIs) were estimated through a random-effects meta-analysis. Results In total, 30 articles were analyzed. According to the meta-analysis, higher adiponectin concentrations were inversely linked to a reduced CRC risk (OR: 0.85, 95% CI: 0.74–0.96), particularly in men. However, no notable connection was detected between higher leptin concentrations and risk of CRC (OR: 1.12, 95% CI: 0.96–1.31). In subgroup analyses, BMI adjustment reinforced the negative association between higher adiponectin levels and risk of CRC, while insulin adjustment yielded non-significant results. Additionally, higher leptin levels revealed a meaningful relationship with colorectal adenoma risk (OR: 1.39, 95% CI: 1.06–1.84), whereas higher levels of adiponectin were not significantly linked to adenoma (OR: 0.79, 95% CI: 0.46–1.36). Conclusion According to this meta-analysis, elevated adiponectin concentrations may play a protective role against CRC, while leptin could potentially contribute to an elevated colorectal adenoma risk. Further studies are required to explore the potential mechanisms underlying adipokine-mediated colorectal carcinogenesis.